Pengaruh Model Project Citizen terhadap Kemampaun Berpikir Kritis dan Komunikasi Siswa Kelas IV SD - Trima Mukti; Anwar Senen (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Project Citizen is a learning model that theoretically has the potential to influence the critical thinking and communication skills of elementary school students in Pancasila Education learning. The purpose of the study was to determine if there was an effect of the model Project Citizen on students' critical thinking and communication skills.mThis research used a quasi-experimental design with the population of all grade IV students of Kapanewon Tanjungsari Cluster III Elementary School. The subject in the study was Mentel II Elementary School as an experimental class, which was a class that received learning treatment using the model Project Citizen, and Mentel I Elementary School as a control class using the Direct Learning model. The instruments used to collect data were in the form of critical thinking ability test questions, communication ability test questions, questionnaires, and observation sheets. The results of the study show that: 1) the hypothesis test of students' critical thinking ability using the independent t-test obtain a significance value (2-Tailed) 0.026 < 0.05 so that it can be concluded that there is an effect of the model Project Citizen on the critical thinking ability of elementary school students; 2) the hypothesis test of students' communication ability using the test independent t-test obtain a significance value (2-Tailed) 0.000 < 0.05 so that it can be concluded that there is an effect of the model Project Citizen to the communication skills of elementary school students; and 3) the MANOVA test showed a significance value of 0.000 < 0.05 so that it can be concluded that there is an effect of the learning model Project Citizen to students' critical thinking and communication skills simultaneously.